Entrainment and Energy Transfer Variability Along the Descending Path of the Denmark Strait Overflow Plume. Issue 4 (22nd April 2018) - North, Ryan P.; Jochumsen, Kerstin; Moritz, Martin
Abstract: The descent of the Denmark Strait overflow plume is an important process in the Atlantic Meridional Overturning Circulation. Downstream of the sill, the plume entrains ambient water, increasing its volume transport. The entrainment and related transfer of energy can be driven by vertical or horizontal turbulent mixing, and varies spatially, as the plume descends, and temporally, as the volume transport at the sill changes. Using over 30 years of profile data, this spatial and temporal variability in the first 200 km downstream of the sill was investigated. Dissipation and entrainment rates were derived from Thorpe scales, and each profile was identified as either a low‐ or high‐transport flow, defined as below or above‐average volume transport at the sill. In the first 175 km flow type explains most of the variability in entrainment and dissipation rates, with high‐transport flow producing order of magnitude higher rates. Sections crossing the plume and yo‐yo casts (continuous profiling) indicate that dissipation and entrainment are likely driven by the formation of shear instabilities in the interfacial layer, when the vertical velocity shear overcomes the stratification. This vertical turbulent mixing explains most of the variability within the first 175 km, suggesting horizontal turbulent mixing processes may not play as important a role in this region. The importance of temporal flow variability means that further improvements to our understanding of plume dynamics in the Denmark Strait will require a novel observational approach to fully account for spatial and temporal contributions. Key Points: Analysis of over 30 years of CTD and LADCP profiles along the descent of the Denmark Strait overflow plume Downstream dissipation and entrainment rates are higher for flows with increased volume transport at the sill Vertical turbulent processes drive dissipation and entrainment in the first 175 km of the plume's descent